2013
DOI: 10.1007/s11255-013-0432-0
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR, MTR and MTRR polymorphisms and risk of chronic kidney disease in Japanese: cross-sectional data from the J-MICC Study

Abstract: The present study found a significant association between the subjects with the T/T genotype of MTHFR C677T polymorphism and the elevated risk of CKD, which may suggest the possibility of the risk evaluation and prevention of this potentially life-threatening disease based on genetic traits in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Another large-scale cross-sectional study in Japan found no significant interaction between MTHFR C677T and blood folate concentration on CKD. [ 116 ] Further stratified analysis found that the risk of developing CKD was higher in subjects with the TT genotype and low blood folate concentration (OR = 2.07, 95% CI = 1.30–3.31). Regarding drug–gene interactions, many RCTs have showed significant interactions between MTHFR C677T and folate supplements.…”
Section: Discussionmentioning
confidence: 99%
“…Another large-scale cross-sectional study in Japan found no significant interaction between MTHFR C677T and blood folate concentration on CKD. [ 116 ] Further stratified analysis found that the risk of developing CKD was higher in subjects with the TT genotype and low blood folate concentration (OR = 2.07, 95% CI = 1.30–3.31). Regarding drug–gene interactions, many RCTs have showed significant interactions between MTHFR C677T and folate supplements.…”
Section: Discussionmentioning
confidence: 99%
“…Logistic regression analysis was performed to estimate age- and sex-adjusted ORs and 95% CIs for CKD by genotype. All other potential confounding variables, including BMI, systolic blood pressure, diastolic blood pressure, fasting plasma glucose, glycated hemoglobin, total cholesterol, HDL cholesterol, triglycerides, uric acid, past history of cardiovascular or cerebrovascular diseases, use of anti-hypertensive, glucose-lowering, or lipid-lowering drugs, smoking status, and drinking habit were tested [ 39 ] to determine if they produced significant CIEs, as described previously [ 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our results showed an association between the MTHFR variant and the resistance index to the erythropoietin. Different studies show that ESRD patients homozygous for the mutant allele rs1801133 have increased mortality risk 76 , and associations of the MTHFR gene with CKD progression have also been reported 77,78 .…”
Section: Scientific Reports |mentioning
confidence: 99%